2016
DOI: 10.1186/s13028-016-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute phase reaction and postoperative stress in pigs undergoing video-assisted thoracoscopic versus thoracotomy pneumonectomy

Abstract: BackgroundVideo-assisted thoracoscopic surgery (VATS) has been used for many thoracic diseases as an alternate approach to thoracotomy. The aim of this study was to compare the surgical outcome of pneumonectomy using VATS with that using thoracotomy pneumonectomy in pigs. Fourteen pigs were equally divided into two groups; one group underwent VATS and the other group underwent transthoracic pneumonectomy. We monitored pre-, intra-, and post-operative physiologic parameters, along with blood cell count, serum C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The increased corticosterone levels observed in our anesthetized and mechanically ventilated control animals suggest that even the anesthetic perioperative management contributes to some degree of surgical stress but, interestingly, the pneumothorax event did not significantly impact corticosterone production when compared to anesthetized control animals, which may indicate no additional significant surgical stress induced by CO 2 -pneumothorax. These findings are in good accordance with the literature since video-assisted thoracic surgery is associated with less tissue injury and consequently reduced acute-phase response and early postoperative stress [31,32]. Nevertheless, most studies do not isolate the surgical approach per se, associating the surgical approach (thoracotomy vs. thoracoscopy) with the surgical procedure and associated organ trauma, which can overlap the stress effect of CO 2 -insufflation.…”
Section: Discussionsupporting
confidence: 85%
“…The increased corticosterone levels observed in our anesthetized and mechanically ventilated control animals suggest that even the anesthetic perioperative management contributes to some degree of surgical stress but, interestingly, the pneumothorax event did not significantly impact corticosterone production when compared to anesthetized control animals, which may indicate no additional significant surgical stress induced by CO 2 -pneumothorax. These findings are in good accordance with the literature since video-assisted thoracic surgery is associated with less tissue injury and consequently reduced acute-phase response and early postoperative stress [31,32]. Nevertheless, most studies do not isolate the surgical approach per se, associating the surgical approach (thoracotomy vs. thoracoscopy) with the surgical procedure and associated organ trauma, which can overlap the stress effect of CO 2 -insufflation.…”
Section: Discussionsupporting
confidence: 85%
“…C-reactive protein and interleukin-6 measurements were significantly lower in the VATS group compared to the open-thoracotomy group on POD 1, and serum cortisol levels for the thoracotomy group were significantly elevated compared to VATS at 4 hours and 1 day after surgery. 24 Beyond the laboratory setting, actual results for thoracoscopic pneumonectomy are largely limited to case reports and case series based on single-institution experiences. The first VATS pneumonectomy (left) was reported by Walker in 1994, followed a year later by results from a series of six patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that VATS is associated with significantly less response in C-reactive protein (CRP) and cytokine levels. Acute-phase proteins (APPs) are a series of proteins that are sensitive to inflammation and body stress including infection, surgical trauma, certain diseases and tissue damage [8,9]. The concentrations of certain APPs, including CRP may increase markedly during stress or under pathological conditions.…”
Section: Introductionmentioning
confidence: 99%